Rapid and simultaneous in situ assessment of aflatoxins and stilbenes using silica plate imprinting mass spectrometry imaging. - Diogo N de Oliveira; Mônica S Ferreira; Rodrigo R Catharino (PLoS ONE)
A fast and direct combination of techniques for simultaneous mycotoxin and phytoalexin identification in peanut skin and kernel is described. Silica Plate Imprinting Laser Desorption/Ionization Mass Spectrometry Imaging (SPILDI-MSI) is a powerful technique that exhibits great advantages, such as solvent-free and matrix-free characteristics, as well as no sample preparation or separation steps. It also permits accurate identification of mycotoxins and phytoalexins with unique fingerprint profiles in just a few seconds. Results are expressed as chemical images of the 4 identified types of aflatoxins (B1, B2, G1 and G2) and a stilbenoid (resveratrol). Also, SPILDI-MSI allows the comparison between the spatial distribution of aflatoxins and resveratrol found in kernel and skin. This novel application has proven to be useful for instantaneous qualitative assessment of aflatoxins and stilbenoids both in the peanut skin and kernel and offers precise tracking of fungal contamination in nuts and other foodstuffs.